Accurate modeling of the diagnostic 118-GHz oxygen line for remote sensing of the atmosphere. (July 2017) - Koshelev, M.A.; Delahaye, T.; Serov, E.A.; Vilkov, I.N.; Boulet, C.; Tretyakov, M.Yu.
Abstract: We report the results of laboratory investigations of the shape of the diagnostic atmospheric N = 1- oxygen line performed over a very wide range of pressures from 0.4 to 1000 Torr using two principally different spectrometers having complementary abilities. A spectrometer with a radio-acoustic detector of absorption was used for recording low pressure spectra spanning the 0.4–2 Torr range, and high pressure data from 250 to 1000 Torr were registered by a resonator spectrometer. The sensitivity of both instruments was improved significantly which allowed us to obtain signal-to-noise ratio at spectra recordings of the order of a few thousands. The spectra analysis enabled the first manifestation of the speed-dependence of the collision cross section of the line, along with considerable refinement of other parameters, including pressure broadening, intensity and line-mixing. The results are of primary importance for atmospheric applications. Highlights: Outstanding SNR is achieved for the 118-GHz diagnostic line recordings in the 0.4-1000 Torr pressure range. Clear manifestation of the SD effect was observed for this line. A new line shape model was developed for taking into account SD and mixing effects. Most accurate line shape parameters were retrieved for atmospheric applications.